(untitled) (Estudios humanísticos. Geografía, historia y arte, 1997)
Several artists working with the same name in Castilian late Gothic sculpture have been traditionally identified as Diego Copín de Holanda. The article tries to separate each one basing on the documents that have been conserved. There are three artist in this case: Master Copín de Ver, working in León cathedral between 1474 and 1504. Master Francisco Copín, working in Burgos between 1482 and 1493 and Master Copín de Holanda, working in Toledo between b. 1500 and a. 1517. The documents about the León artist, now published, contribute to clarify this problem.